(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Nanofluids have been employed in a variety of practical applications within the field of heat transfer. There are numerous applications for cooling lubricants, including vehicle radiators, solar and nuclear energy systems, biomedical devices, heating, ventilating, conditioning of air, storage refrigeration, engine cooling, and transformers. The effects of unconventional fluids when combined with traditional fluids for heat transfer have been the subject of extensive scientific research. The results of these studies have demonstrated that the combination enhances heat transfer performance to a level that surpasses that of conventional working fluids. These investigations collectively demonstrate that nanofluids are capable of exceptional heat transfer. It is necessary to adopt a comprehensive approach that integrates both practical application and conceptualization in order to optimize the efficacy of flat plate solar collectors. The results of this study show that the potential for efficiency improvements to range from twenty percent to eighty-five percent can be achieved by increasing the concentration of nanofluids and the bulk flow rate. This paper aims to summarize the scientific progress made in the field of application of nanofluids to enhance the thermal performance of flat plate solar collectors.